Persepsi Peserta Didik terhadap Metode Mengajar Pendidikan Agama Islam: Studi Kasus Tiga SMPN di Kota Makassar - Abd Haris (Journal on Education, 2024)
This study examines students' perceptions of teaching methods in Islamic religious education at three public junior high schools (SMPN) in Makassar. The aim of this research is to understand students' perceptions of teaching methods in Islamic religious education at SMP Negeri 6, SMP Negeri 8, and SMP Negeri 23 in Makassar. This research is a field study. Data collection methods include observation, questionnaires, interviews, and documentation. The findings of the study are as follows: 1) Students perceive positively the mastery of materials, applied teaching methods, varied learning methods, the use of information technology media in teaching, motivation in practicing worship, the field of Islamic religious education, the imposition of sanctions, assignment tasks, and learning models that actively involve students. 2) Students perceive negatively about teaching methods that are not varied, teaching methods that do not use information technology media, and learning models that do not actively involve students.